Contaminación del agua y su incidencia en la calidad de vida de habitantes y visitantes en la ciudad Quevedo, año 2021 - Ponce Franco, Johanna Liseth (2021)
The main objective of this research work was to analyze how water pollution affects the quality of life of the inhabitants and visitors of the city of Quevedo. The applied research technique was direct observation with the help of surveys, the instrument used was the questionnaire which consisted of various closed and pre-prepared questions. The sample was taken through the probabilistic formula where it gave a total of 50 people. The chosen method was the deductive one that served to determine the specific indicators that later helped to give the respective conclusions of the topic, the inductive method was effected after carrying out the study, for its part the analytical method allowed to understand the situation in which it was he found the city of Quevedo. The results were tabulated where the graphs were made considering the respective analysis and interpretation, later the detected situations were described to also later reveal the appropriate solutions.